UPAYA MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI MEDIA KARTU ANGKA BERGAMBAR PADA ANAK KELOMPOK A RA MUSLIMAT NU KHALIMATUS SA'DIYAH - Sumarni, Sumarni; Prasetyo, Agus Fathoni (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: The problem of this research is to seek to increase the ability to recognize number symbols through the media of illustrated number cards in the children of Group A RA Muslimat Nu Khalimatus Sa'diyah Panyuran-Palang-Tuban for the 2020/2021 academic year. The theories used as the basis in the implementation of this research include the theory of understanding number symbols, and the media of picture number cards. This research is expected to provide answers to the formulation of the problem (1) How is the ability to recognize number symbols in the Children of Group A RA Muslimat NU Khalimatus Sa'diyah Panyuran, Palang District, Tuban Regency for the 2020/2021 Academic Year? (2) How is the application of illustrated number card media in the ability to recognize symbols in Children of Group A RA Muslimat NU Khalimatus Sa'diyah Panyuran, Palang District, Tuban Regency, 2020/2021 Academic Year? (3) How to increase the ability to recognize number symbols using pictorial number card media for Children of Group A RA Muslimat NU Khalimatus Sa'diyah Panyuran, Palang District, Tuban Regency, 2020/2021 Academic Year? This research uses classroom action research. Based on the research findings, it is recommended: (1) Educators can use illustrated number card media as an alternative in learning to improve children's ability to recognize number symbols. (2) Principals provide facilities and support teachers' efforts in using illustrated number card media to develop children's ability to recognize number symbols.